Case Report: 25-year-old Female at Term Labour and Normal Delivery - Pradnya Gavhale; Vaishali Taksande; Shalini Moon (Institute of Medico-legal Publications Pvt Ltd, 2021)
Labor has been defined as that of the initiation of periodic painful contractions of progressive deletion aswell as dilation of a cervix, followed by a decent part going to lead to the expulsion of its fetus & placentafrom the uterus of mother. Post - natal treatment was its individualized treatment provided that meet theneeds of the baby and mother after delivery/childbirth.Case Report –Mrs. Nikita Matram 25-year-old female was admitted in AVBR Hospital with the complaintof pain in abdomen and increased the fetal movement on date 4/01/2020 and she delivered female baby ondate 6/01/2020 and the baby weight was 2.8 kg at 1:40 am now her complaint was pain on suture side andweakness. But the patient has a previous history of abortion after marriage of four month two and half monthof baby was abort. That time dilatation and curettage was done.Discussion – Patient delivered female baby throughout the vaginal delivery and baby and mother wasnormal after delivery baby was kept with mother on same bed and initiate breastfeeding within one hourafter delivery.Conclusion – Case report conclude that after normal delivery and post-natal care mother and baby wasnormal.